The Influence of Creative Messages in Digital Media Advertising (Liputan6.Com) in Increasing Housewife to Read the News - Syahla Nur Fitri; Wahyunengsih Wahyunengsih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Creative advertisements are advertisements that are considered original or not imitating others, advertisements that are astonishing, unexpected, meaningful and affect emotions. Creative advertising makes the audience pay attention to the advertisement in detail and detail. This article focuses on the effect of creative advertising on housewives in reading the news. This study uses a qualitative method with a questionnaire approach. The object of this research is housewives and the purpose of this study is to find out whether creative advertising can influence housewives to read the news. The results of the research in the form of creative advertisements on liputan6.com can influence a person's attitudes and behavior in terms of messages, content to the audience, especially in reading news